2007
DOI: 10.1002/pts.783
|View full text |Cite
|
Sign up to set email alerts
|

Effects of film forming and hydrophobic properties of starches on surface sized packaging paper

Abstract: The effect on mechanical and barrier properties upon addition of glycerol to temperature-responsive hydrophobically modified (HM) potato starch was studied on free films. The addition of glycerol lowered the glass transition temperature, the storage modulus, and the water vapor permeability (WVP) for the HM starch films. The HM starch phase separates upon cooling below an upper critical temperature into a solid and a liquid phase. Adding glycerol to the warm starch solution had an inhibiting effect on the part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 17 publications
3
25
0
Order By: Relevance
“…Therefore, tapioca and corn starch had the lowest inhibition activity. Moreover, this might be a result of the low permeability of large peppermint oil molecules into the environment because starch film has been reported to be an efficient gas barrier because it can block the transportation of the smallest of gas molecules such as oxygen and carbon dioxide owing to its crystalline structure (Jonhed and others ). Usually, in the presence of oxygen, AC has a hydrophilic surface imparted by the oxygen containing a functional group, and its pore structure has an affinity to water that subsequently adsorbs moist vapour into the system.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, tapioca and corn starch had the lowest inhibition activity. Moreover, this might be a result of the low permeability of large peppermint oil molecules into the environment because starch film has been reported to be an efficient gas barrier because it can block the transportation of the smallest of gas molecules such as oxygen and carbon dioxide owing to its crystalline structure (Jonhed and others ). Usually, in the presence of oxygen, AC has a hydrophilic surface imparted by the oxygen containing a functional group, and its pore structure has an affinity to water that subsequently adsorbs moist vapour into the system.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is clearly seen that the water absorption was drastically decreased when only the polymeric coating agent without any nano-RHS composition was used. This is because the paper surface was covered by a film layer formed by the polymeric phase of such a coating agent, preventing water absorption [36]. On the contrary, when nano-RHS in different proportions was used, the subsequent coating agents increased the water absorption as the amount of nano-RHS in the coating agent increased.…”
Section: Physical Properties and Appearance Of Nano-rhs Coated Bleachmentioning
confidence: 91%
“…When comparing the different formulations, it was observed that WVTR decreased as the proportion of starch decreased and latex content increased. In general, the WVTR values are consistently in the same scale as reported for similar starch-based coatings [22]. The analysis setup was specifically designed to position the coated side of the paperboard towards the penetrant (water vapor) to minimize error caused by the paperboard's large thickness and porosity.…”
Section: Water Vapor and Oxygen Transmission Ratementioning
confidence: 97%
“…The challenge with biopolymer materials is their runnability on the coating unit, film formation properties, and film products' high affinity for water and water vapor. Therefore, studies of the physico-chemical and barrier properties of biopolymers, starch, and starch blends as coating materials are widely performed [3,[20][21][22][23][24][25]. Thorough studies have been performed to identify the best formulations for coating processability [5] and an improved grease barrier [5,26,27].…”
Section: Introductionmentioning
confidence: 99%